Micromammals from the late early Miocene of Çapak (western Anatolia) herald a time of change. (September 2021) - Bilgin, Melike; Joniak, Peter; Mayda, Serdar; Göktaş, Fikret; Peláez-Campomanes, Pablo; van den Hoek Ostende, Lars W.
Abstract: The new fossil micromammal assemblage of Çapak represents a mixture of both Anatolian and European faunal elements. The locality is very important for understanding faunal evolution in the less well-known time interval at the end of the early Miocene of western Anatolia. In Çapak, nine species of rodents and one species of ochotonid were encountered: the hamsters Democricetodon gracilis, Megacricetodon primitivus, Eumyarion aff. E . montanus, Cricetodon cf. C . aliveriensis, Cricetodon sp., and Karydomys cf. K . strati, the mole-rat Debruijnia sp., the squirrel Aliveria luteyni, the dormouse Myomimus tanjuae n. sp., and the pika Albertona balkanica . The assemblage is referable to Anatolian local zone E or MN unit 4. The relative abundance of the various genera is markedly different from that of the older early Miocene assemblages, suggesting that the environment in Anatolia became drier and had a more open landscape. UUID: http://zoobank.org/75f3276c-dcd8-4090-b2f6-d8fc8d3c3f7c